2014
DOI: 10.1002/acn3.120
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of NMDA receptor IgA/IgM antibodies in different dementia types

Abstract: ObjectiveTo retrospectively determine the frequency of N-Methyl-D-Aspartate (NMDA) receptor (NMDAR) autoantibodies in patients with different forms of dementia.MethodsClinical characterization of 660 patients with dementia, neurodegenerative disease without dementia, other neurological disorders and age-matched healthy controls combined with retrospective analysis of serum or cerebrospinal fluid (CSF) for the presence of NMDAR antibodies. Antibody binding to receptor mutants and the effect of immunotherapy wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
4
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(128 citation statements)
references
References 35 publications
(52 reference statements)
4
107
4
5
Order By: Relevance
“…28 While irrespective of the epitope, all 14 NMDAR1-AB-positive sera investigated here (IgM, IgG, IgA) revealed similar AB functionality (internalization, electrophysiology), the AB-inducing factors may have determined the epitopes via mechanisms like molecular mimicry. 29,30 Published work on NMDAR1-AB epitopes is scarce 25,31,32 and focused on IgG recognizing NTD and the NTD-G7 domain (N 368 /G 369 ), probably because this region and Ig class was first deemed pathognomonic for anti-NMDAR-encephalitis. 5,25 Indeed, the sera investigated here of two young females with diagnosed anti-NMDAR-encephalitis, originally reported within a series of schizophrenia cases, 8 also recognized this epitope, however, without sticking out functionally (that is, regarding internalization or electrophysiology).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 While irrespective of the epitope, all 14 NMDAR1-AB-positive sera investigated here (IgM, IgG, IgA) revealed similar AB functionality (internalization, electrophysiology), the AB-inducing factors may have determined the epitopes via mechanisms like molecular mimicry. 29,30 Published work on NMDAR1-AB epitopes is scarce 25,31,32 and focused on IgG recognizing NTD and the NTD-G7 domain (N 368 /G 369 ), probably because this region and Ig class was first deemed pathognomonic for anti-NMDAR-encephalitis. 5,25 Indeed, the sera investigated here of two young females with diagnosed anti-NMDAR-encephalitis, originally reported within a series of schizophrenia cases, 8 also recognized this epitope, however, without sticking out functionally (that is, regarding internalization or electrophysiology).…”
Section: Discussionmentioning
confidence: 99%
“…33 Regarding NMDAR1-AB of the IgA class, a single study, mapping epitopes of two female patients, found in one of them evidence of NTD/G7 as a target epitope (likely among other epitopes). 31 Interestingly, the significance of AB for brain manifestation of lupus erythematosus seems still debatable. In a recent study, lack of B cells and autoantibodies in a murine model of systemic lupus did not prevent the development of key features of neuropsychiatric lupus.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to IgG antibody which has high disease specificity of anti-NMDAR encephalitis [21], IgA and IgM antibodies may be elevated in healthy individuals and many disease carriers, ranging from major depression and schizophrenia [42] to hypertension, diabetes and stroke [83] and to multiple sclerosis (MS) [84], dementia [85, 86], Alzheimer's and Parkinson's disease [87, 88]. Those patients with high levels of IgA and IgM antibodies may potentially benefit from immunotherapy.…”
Section: Anti-nmdar Antibodiesmentioning
confidence: 99%
“…Importantly, anti-NMDAR encephalitis and the associated psychotic symptoms are caused specifically by IgG antibodies recognizing the GluN1 subunit of the NMDAR (Dalmau et al, 2008). The clinical significance of IgG antibodies that target other NMDAR subunits or of IgA or IgM subtypes recognizing NMDARs is unknown, though connections have been made between these subtypes and dementia and viral encephalitis (Doss et al, 2014;Prüss et al, 2012aPrüss et al, , 2012b. Examination of serum obtained at symptom onset from 80 patients with new-onset psychosis who 1 year later met criteria for schizophrenia-spectrum illness revealed no presence of IgG GluN1 antibodies in either patients or controls (Masdeu et al, 2012).…”
Section: Anti-nmdar Antibodies and Psychosismentioning
confidence: 99%